Current collector, method for producing same, electrode, and battery
By forming a coating containing a specific vinylidene fluoride polymer and a conductive additive on the substrate of the current collector, the problem of cracks in the composite material layer is easily encountered in the electrode manufacturing, and high-quality and stable electrode manufacturing is achieved.
Patent Information
- Application Number
- CN202380065053.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-29
- Filing Date
- 2023-09-19
- Publication Date
- 2025-04-18
AI Technical Summary
When producing the electrode, if a layer containing acid-modified polyvinylidene fluoride and a copolymer of acrylic acid and vinylidene fluoride is formed between the conductive substrate and the composite material layer, cracks are prone to occur in the composite material layer.
The vinylidene fluoride polymer A containing structural units derived from vinylidene fluoride and structural units derived from specific compounds, and a coating of conductive additives, is used as a coating on the substrate of the current collector to reduce the risk of cracking of the composite material layer.
It effectively prevents cracks in the composite material layer, improves the quality and stability of the electrode, making it suitable for use in various lithium-ion secondary batteries.
Smart Images

Figure BDA0005304381570000021 
Figure BDA0005304381570000022 
Figure BDA0005304381570000031
Abstract
Description
Technical Field
[0001] The present invention relates to a current collector and a method for producing the same, an electrode and a battery. Background Art
[0002] Lithium ion secondary batteries are widely used in various electronic devices, electric vehicles, etc. An electrode of a lithium ion secondary battery generally includes a current collector and a composite material layer including an active material and a binder disposed on the current collector.
[0003] In recent years, the high capacity of lithium ion secondary batteries is needed. For example, attempts have been made to increase the capacity of lithium ion secondary batteries by high voltage charging. In addition, a conductive layer (hereinafter also referred to as "conductive layer") is formed between the current collector and the composite material layer to reduce the interface resistance between the current collector and the composite material layer. For example, it has been proposed to provide a layer comprising polyvinylidene fluoride, polyvinyl pyrrolidone, and powdered carbon material acid-modified by methyl acrylate, methyl methacrylate, etc. on the surface of the current collector (Patent Document 1). In addition, a current collector is also proposed, which is provided with a resin layer comprising a copolymer of acrylic acid and vinylidene fluoride and conductive particles on the surface of a conductive substrate (Patent Document 2).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 6529700
[0007] Patent Document 2: International Publication No. 2013 / 151046 Summary of the invention
[0008] Problems to be solved by the invention
[0009] However, after intensive research, the inventors found that when making an electrode, if a layer comprising the acid-modified polyvinylidene fluoride described in Reference 1 or the copolymer of acrylic acid and vinylidene fluoride described in Reference 2 is formed between the conductive substrate and the composite material layer, cracks are likely to occur in the composite material layer when making the electrode.
[0010] Therefore, an object of the present invention is to provide a current collector in which a composite material layer is less likely to crack when manufacturing an electrode, a method for manufacturing the same, and an electrode and a battery using the current collector.
[0011] Solutions for solving problems
[0012] The present invention provides a collector, wherein the collector comprises: a substrate comprising a metal; and a coating disposed on at least one surface of the substrate, the coating comprising: a vinylidene fluoride polymer A comprising a structural unit derived from vinylidene fluoride and a structural unit derived from a compound represented by the following general formula (1), and a conductive aid.
[0013] [Chemical formula 1]
[0014]
[0015] (In the general formula (1), R 1 , R 2 and R 3 Each independently represents a hydrogen atom, a chlorine atom, a fluorine atom or an alkyl group having 1 to 5 carbon atoms, and X 1 It represents a divalent atomic group having a main chain atom number of 1 to 6 and a molecular weight of 156 or less).
[0016] Furthermore, the present invention provides an electrode comprising the above-mentioned current collector and a composite material layer including an active material and a binder disposed on the coating layer of the current collector.
[0017] Furthermore, the present invention provides a battery having the above-mentioned electrode.
[0018] The present invention provides a method for producing a current collector, comprising the step of coating a coating liquid comprising a vinylidene fluoride polymer a and a solvent on at least one surface of a substrate comprising a metal, wherein the vinylidene fluoride polymer a comprises a structural unit derived from vinylidene fluoride and a structural unit derived from a compound represented by the following general formula (1a).
[0019] [Chemical formula 2]
[0020]
[0021] (In the general formula (1a), R 1a , R 2a and R 3a Each independently represents a hydrogen atom, a chlorine atom, a fluorine atom or an alkyl group having 1 to 5 carbon atoms, and X 1a It represents a divalent atomic group having a main chain atom number of 1 to 6 and a molecular weight of 156 or less).
[0022] Effects of the Invention
[0023] Even if a composite material layer is formed on the current collector of the present invention, the composite material layer is unlikely to crack. Therefore, the current collector and the electrode using the current collector are suitable as components of various lithium ion secondary batteries. DETAILED DESCRIPTION
[0024] 1. Current Collector
[0025] The current collector of the present invention is a current collector for lithium ion secondary batteries, etc., and is usually used by forming a composite material layer on the current collector. In addition, the current collector of the present invention has: a substrate comprising a metal; and a coating disposed on at least one surface of the substrate, the coating comprising: a vinylidene fluoride polymer A comprising a structural unit derived from vinylidene fluoride and a structural unit derived from a compound represented by the following general formula (1), and a conductive auxiliary agent.
[0026] [Chemical formula 3]
[0027]
[0028] (In the general formula (1), R 1 , R 2 and R 3 Each independently represents a hydrogen atom, a chlorine atom, a fluorine atom or an alkyl group having 1 to 5 carbon atoms, and X 1 It represents a divalent atomic group having a main chain atom number of 1 to 6 and a molecular weight of 156 or less).
[0029] As described above, in a current collector having a coating layer comprising a copolymer of vinylidene fluoride and acrylic acid and monomethyl maleate formed on a substrate, when a composite material layer is formed on the coating layer, cracks are easily generated on the surface of the composite material layer. The reason is not clear, but it can be inferred as follows.
[0030] It is believed that when the copolymer of acrylic acid, monomethyl maleate, etc. and vinylidene fluoride is dissolved or dispersed in the presence of a conductive aid, when the solvent evaporates, it has a very easy cohesive property (cohesion). The cohesion is believed to be due to the structural unit derived from vinylidene fluoride and the carboxyl group derived from acrylic acid, monomethyl maleate, etc. being arranged close to each other. When a composite material slurry (a composition for forming a composite material layer) is applied on a coating comprising such a copolymer, a part of the above-mentioned copolymer will be dissolved in the solvent in the composite material slurry. Then, the dissolved copolymer will cohere when the solvent evaporates again and precipitates, and an island-like region will be formed on the surface of the substrate. As a result, strain is generated inside the composite material layer formed thereon, and it is believed that cracks will appear on the surface of the composite material layer.
[0031] In contrast, in the copolymer of the compound represented by the general formula (1) and vinylidene fluoride, the structural unit derived from vinylidene fluoride and the carboxyl group position derived from the compound represented by the general formula (1) are arranged relatively far apart. Therefore, even if dissolved in the solvent in the composite material slurry, it is not easy to produce a large cohesive force and it is not easy to form the above-mentioned island region. As a result, it is believed that the surface of the obtained composite material layer is not easy to crack.
[0032] Hereinafter, the structure of the current collector of the present invention will be described in detail.
[0033] (1) Base material
[0034] The substrate is a composition of the base of the current collector, as long as the substrate has sufficient conductivity and contains metal. The substrate may contain only metal, or may contain materials other than metal (such as resin, ceramic, etc.). The substrate is more preferably composed of only metal. Here, the type of metal contained in the substrate is appropriately selected according to the type and shape of the battery. The substrate may contain only one metal, or may contain two or more metals. Examples of metals contained in the substrate include aluminum, copper, iron, stainless steel, steel, nickel, titanium, etc.
[0035] In addition, the shape of the substrate is appropriately selected according to the type and size of the battery. The substrate may be, for example, a foil or a metal mesh of the above-mentioned metal. In addition, the substrate may also be a material formed by laminating the above-mentioned metal foil or metal mesh on the surface of a material other than a metal.
[0036] (2) Coating
[0037] The coating layer only needs to contain at least the vinylidene fluoride polymer A and the conductive additive, and may contain other components as required. When the coating layer contains the vinylidene fluoride polymer A and the conductive additive, the electrical resistance between the substrate and the composite material layer can be reduced.
[0038] · Vinylidene fluoride polymer A
[0039] The vinylidene fluoride polymer A is a polymer containing a structural unit derived from the above-mentioned vinylidene fluoride and a structural unit derived from a compound represented by the general formula (1) described later. The coating layer may contain only one type of the vinylidene fluoride polymer A, or may contain two or more types.
[0040] The vinylidene fluoride polymer A may contain only structural units derived from vinylidene fluoride and structural units derived from the compound represented by the general formula (1), or may partially contain structural units derived from compounds other than these.
[0041] The amount of the structural unit derived from vinylidene fluoride in the vinylidene fluoride polymer A is preferably 90.0 mol% or more and 99.99 mol% or less, more preferably 93.0 mol% or more and 99.98 mol% or less, and particularly preferably 96.0 mol% or more and 99.97 mol% or less relative to the amount (mol) of all the structural units constituting the vinylidene fluoride polymer A. When the amount of the structural unit derived from vinylidene fluoride is 90.0 mol% or more, the properties derived from vinylidene fluoride, such as electrochemical stability, are easily obtained in the coating. The amount of the structural unit derived from vinylidene fluoride in the vinylidene fluoride polymer A can be determined by, for example 19 This can be determined by F-NMR analysis or the like.
[0042] Next, the general formula (1) is shown below: The vinylidene fluoride polymer A may contain only one type of structural unit derived from the compound represented by the general formula (1) above, or may contain two or more types.
[0043] [Chemical formula 4]
[0044]
[0045] In the above general formula (1), R 1 , R 2 and R 3 Each independently represents a hydrogen atom, a chlorine atom, a fluorine atom or an alkyl group having 1 to 5 carbon atoms. 1 and R 2 It is preferably a substituent with little steric hindrance, preferably hydrogen or an alkyl group having 1 to 3 carbon atoms, more preferably hydrogen or a methyl group.
[0046] In addition, X in the above general formula (1) 1 represents a divalent atomic group having a main chain atom number of 1 to 6 and a molecular weight of 156 or less. 1 The number of atoms in the main chain of refers to the number of atoms in the shortest chain connecting the terminal carboxyl group and -C(=O)O- group in the above general formula (1). 1 When the number of atoms in the main chain of the atomic group represented is 1 or more, as described above, even if the vinylidene fluoride polymer A is dissolved in a solvent, it is not easy to generate a large cohesive force, and the composite material layer is not easy to crack. On the other hand, when the number of atoms in the main chain is 6 or less, the copolymerizability with vinylidene fluoride is good.
[0047] The above X 1 The structure of the atomic group represented is not particularly limited as long as its molecular weight is less than 156 and satisfies the number of atoms in the above-mentioned main chain, and it can be straight-chain, branched, or contain a ring structure. Examples of the structure constituting the above-mentioned atomic group include alkylene, carbonyl (-C(=O)-, ether bond (-O-), aromatic ring, and alicyclic structure.
[0048] Specific examples of the compound represented by the general formula (1) include carboxymethylacrylate, carboxymethylmethacrylate, 2-carboxyethyl acrylate, 2-carboxyethyl methacrylate, succinic acid acryloxyethyl, succinic acid methacryloyloxyethyl, phthalic acid acryloxyethyl, phthalic acid methacryloyloxyethyl, succinic acid acryloxypropyl, succinic acid methacryloyloxypropyl, etc. Among them, 2-carboxyethyl acrylate, 2-carboxyethyl methacrylate, succinic acid acryloxyethyl, succinic acid methacryloyloxyethyl, succinic acid acryloxypropyl, succinic acid methacryloyloxypropyl, succinic acid methacryloyloxypropyl, etc. are particularly preferred because they have excellent copolymerizability with vinylidene fluoride and the composite material layer formed on the coating layer is less likely to crack.
[0049] Relative to the amount (moles) of all structural units constituting the vinylidene fluoride polymer A, the amount of structural units derived from the compound represented by the above-mentioned general formula (1) in the vinylidene fluoride polymer A is preferably 0.01 mol% or more and 10.0 mol% or less, more preferably 0.02 mol% or more and 7.0 mol% or less, and particularly preferably 0.03 mol% or more and 4.0 mol% or less. When the amount of structural units derived from the compound represented by the general formula (1) is 0.01 mol% or more, the bonding strength between the coating and the substrate and the bonding strength between the coating and the composite material layer are improved. On the other hand, when the amount of structural units derived from the compound represented by the general formula (1) is 10.0 mol% or less, the amount of structural units derived from vinylidene fluoride is relatively increased, and the electrochemical stability of the coating tends to become good. The amount of structural units derived from the compound represented by the general formula (1) in the vinylidene fluoride polymer A can be adjusted by 19 F-NMR, 1 H-NMR and other analyses.
[0050] In addition, the vinylidene fluoride polymer A may partially contain structural units of compounds other than vinylidene fluoride and compounds derived from the compound represented by the general formula (1) (hereinafter also referred to as "other compounds") within the scope that does not impair the purpose and effect of the present invention. Among them, the amount of structural units derived from other compounds is preferably 9.99 mol% or less relative to the amount (molar) of all structural units constituting the vinylidene fluoride polymer A. When the amount of structural units derived from other compounds in the vinylidene fluoride polymer A is 9.99 mol% or less, the electrochemical stability of the coating becomes good, and the bonding strength between the coating and the substrate is easily improved. The amount of structural units derived from other compounds can be adjusted by 19 F-NMR, 1 Analyze by H-NMR etc.
[0051] Examples of other compounds include fluorine compounds other than vinylidene fluoride, such as vinyl fluoride, trifluoroethylene, tetrafluoroethylene, chlorotrifluoroethylene, hexafluoropropylene, hexafluoroethylene, fluoroalkyl vinyl ether, perfluoromethyl vinyl ether, and perfluoroalkyl vinyl ether; monomethyl maleate (MMM), acrylic acid (AA), methacrylic acid, etc.
[0052] Here, the inherent logarithmic viscosity of vinylidene fluoride polymer A is preferably 1.0 or more, more preferably 1.3dL / g or more, and further preferably 2.0dL / g or more. When the inherent logarithmic viscosity is as described above, the bonding strength between the coating and the substrate, and the bonding strength between the coating and the composite material layer formed on the coating are easily improved. The above-mentioned inherent logarithmic viscosity can be measured by the following method. First, 80mg of vinylidene fluoride polymer A is dissolved in 20mL of N,N-dimethylformamide, and the viscosity is measured using an Ubbelohde viscometer in a thermostatic bath at 30°C. Then, according to the obtained value, based on the following formula, the inherent logarithmic viscosity (η i ).
[0053] η i =(1 / C)·ln(η / η 0 )
[0054] It should be noted that η in the above formula is the viscosity of the solution, η 0 is the viscosity of the solvent N,N-dimethylformamide alone, and C is the concentration of the vinylidene fluoride polymer A, which is 0.4 g / dL.
[0055] The method for preparing the vinylidene fluoride polymer A is not particularly limited, and vinylidene fluoride and the compound represented by the general formula (1) may be polymerized by a known method. Examples of the polymerization method include suspension polymerization, emulsion polymerization, solution polymerization, and the like.
[0056] With regard to the amount of the vinylidene fluoride polymer A in the coating, when the total amount of the vinylidene fluoride polymer A and the conductive aid in the coating is set to 100 parts by mass, it is preferably less than 65 parts by mass, more preferably less than 60 parts by mass, and more preferably less than 55 parts by mass. When the amount of the vinylidene fluoride polymer A is within the above range, when a composite material layer is formed on the coating, the vinylidene fluoride polymer A is not easy to further affect the composite material layer, and a high-quality composite material layer can be easily obtained. In addition, the amount of the vinylidene fluoride polymer A is preferably more than 5 parts by mass, more preferably more than 15 parts by mass, and more preferably more than 25 parts by mass. When the amount of the vinylidene fluoride polymer A is within the above range, the bonding strength between the substrate and the coating, and the bonding strength between the coating and the composite material layer are easily good.
[0057] Conductive additives
[0058] The conductive aid serves to electrically connect the active material in the substrate and the composite material layer. As the conductive aid, a known conductive aid can be used. Specific examples of conductive aids include acetylene black, ketjen black, carbon black, graphite powder, graphene, carbon nanofibers, carbon nanotubes, carbon fibers, and metal powders. The coating may contain only one conductive aid, or may contain two or more.
[0059] When the total amount of the vinylidene fluoride polymer A and the conductive aid in the coating is set to 100 parts by mass, the amount of the conductive aid in the coating is preferably more than 35 parts by mass, more preferably more than 40 parts by mass, and more preferably more than 45 parts by mass. When the amount of the conductive aid is more than 45 parts by mass, it is easy to reduce the resistance between the substrate and the composite material layer. In addition, when the total amount of the vinylidene fluoride polymer A and the conductive aid in the coating is set to 100 parts by mass, the amount of the conductive aid in the coating is preferably less than 95 parts by mass. When the amount of the conductive aid is less than 95 parts by mass, the amount of the vinylidene fluoride polymer A becomes relatively more, and the bonding strength between the substrate and the coating, and the bonding strength between the coating and the composite material layer are easily improved.
[0060] ·other
[0061] In addition to the above-mentioned vinylidene fluoride polymer A and the conductive aid, the coating may also include other components within the scope of not damaging the purpose and effect of the present invention. Examples of other components include known dispersants such as acrylic copolymers, carboxymethyl cellulose, polyvinyl alcohol, polyvinyl pyrrolidone. Furthermore, it may further include: nitrogen compounds such as phosphorus compounds, sulfur compounds, organic acids, amine compounds and ammonium compounds; coupling agents of organic esters, various silane systems, titanium systems and aluminum systems; resins such as polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR) and polyacrylonitrile (PAN). Wherein, when the total amount of the vinylidene fluoride polymer A and the conductive aid in the coating is set to 100 parts by mass, the amount of the other components is preferably less than 10 parts by mass, more preferably less than 5 parts by mass.
[0062] Physical properties of coating
[0063] In addition, the coating layer can be arranged on one surface of the substrate or on both surfaces. In addition, the coating layer can be arranged on one surface of the substrate in a pattern, but from the viewpoint of suppressing cracks in the composite material layer and reducing the resistance between the composite material layer and the substrate, it is preferably arranged in a manner that fully covers one surface or both surfaces of the substrate.
[0064] The thickness of the coating on at least one surface of the substrate is preferably 0.5 μm or more and 10 μm or less, more preferably 0.8 μm or more and 5 μm or less. When the thickness of the coating is 0.5 μm or more, the bonding strength between the coating and the composite material layer is easy to be good. On the other hand, by setting the thickness of the coating to 10 μm or less, the energy density of the battery using the coating can be increased.
[0065] (3) Method for manufacturing current collector
[0066] The method for manufacturing the current collector of the present invention is not particularly limited as long as it is a method that can form a coating on the above-mentioned substrate, but preferably includes a process of applying a coating liquid to at least one surface of the above-mentioned substrate (hereinafter also referred to as a "coating process") and a process of drying the coating liquid (hereinafter also referred to as a "drying process"). Each process is described below.
[0067] Coating process
[0068] The coating liquid applied in the coating step may contain at least the vinylidene fluoride polymer a, a solvent, and a conductive auxiliary agent, and may further contain a dispersant or the like.
[0069] The vinylidene fluoride polymer a contained in the coating liquid includes a structural unit derived from vinylidene fluoride and a structural unit derived from a compound represented by the following general formula (1a).
[0070] [Chemical formula 5]
[0071]
[0072] In the above general formula (1a), R 1a , R 2a and R 3a Each independently represents a hydrogen atom, a chlorine atom, a fluorine atom or an alkyl group having 1 to 5 carbon atoms. 1a , R 2a and R 3a R in the above general formula (1) 1 , R 2 and R 3 In addition, X in the general formula (1a) 1a represents a divalent atomic group having 1 or more and 6 or less atoms in the main chain and a molecular weight of 156 or less, and X in the above general formula (1) 1 That is, the compound represented by the above general formula (1a) is equivalent to the compound represented by the above general formula (1).
[0073] The inherent logarithmic viscosity of the vinylidene fluoride polymer a (vinylidene fluoride polymer A) is preferably 1.0 dL / g or more, more preferably 1.3 dL / g or more, and further preferably 2.0 dL / g or more. When the inherent logarithmic viscosity is above the above value, the bonding strength between the obtained coating and the composite material layer arranged on the coating is easily improved.
[0074] In addition, when the total amount of the vinylidene fluoride polymer a and the conductive aid in the coating liquid is set to 100 parts by mass, the amount of the vinylidene fluoride polymer a in the coating liquid is preferably 65 parts by mass or less, more preferably 60 parts by mass or less, and further preferably 55 parts by mass or less. When the amount of the vinylidene fluoride polymer a is within the above range, the amount of the conductive aid is relatively sufficient. In addition, the amount of the vinylidene fluoride polymer a is preferably 5 parts by mass or more, more preferably 15 parts by mass or more, and further preferably 25 parts by mass or more. When the amount of the vinylidene fluoride polymer a is within the above range, the vinylidene fluoride polymer a can fully bond the conductive aid, while improving the bonding strength between the substrate and the coating, while making it easy to improve the bonding strength between the coating and the composite material layer.
[0075] On the other hand, the conductive aid contained in the coating liquid is the same as the above-mentioned conductive aid. When the total amount of the vinylidene fluoride polymer a and the conductive aid in the coating liquid is set to 100 parts by mass, the amount of the conductive aid in the coating liquid is preferably 35 parts by mass or more, more preferably 40 parts by mass or more, and more preferably 45 parts by mass or more. When the amount of the conductive aid is within the above range, it is easy to obtain a coating with low resistance. In addition, when the total amount of the vinylidene fluoride polymer a and the conductive aid in the coating liquid is set to 100 parts by mass, the amount of the conductive aid in the coating liquid is preferably 95 parts by mass or less, more preferably 85 parts by mass or less, and more preferably 80 parts by mass or less. When the amount of the conductive aid is within the above range, the amount of the vinylidene fluoride polymer becomes sufficient relatively.
[0076] The solvent contained in the coating liquid can be used as long as the above-mentioned vinylidene fluoride polymer a and the conductive aid are uniformly dispersed or dissolved. Examples of the solvent include: water; amide compounds such as dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone; alcohols such as methanol, ethanol, isopropanol, 2-ethyl-1-hexanol, 1-nonanol, lauryl alcohol, tripropylene glycol; amine compounds such as o-toluidine, m-toluidine, p-toluidine; 1-ethyl-3-methylimidazolium bis (trifluoromethylsulfonyl) imide; lactones such as γ-butyrolactone and δ-butyrolactone; sulfoxide / sulfone compounds such as dimethyl sulfoxide and cyclopentane sulfone, etc. The coating liquid may contain only one solvent or more than two solvents. Among them, N-methylpyrrolidone is preferred in that it can easily dissolve the vinylidene fluoride polymer a.
[0077] The amount of the solvent is appropriately selected depending on the type of solvent, the desired viscosity of the coating solution, etc., but is usually preferably 1000 parts by mass or more and 10000 parts by mass or less, and more preferably 3000 parts by mass or more and 7000 parts by mass or less, relative to 100 parts by mass of the total amount of the vinylidene fluoride polymer a and the conductive aid.
[0078] The method for applying the coating liquid to the substrate is not particularly limited, and a doctor blade method, a reverse roll method, a comma roll method, a gravure printing method, an air knife method, a die coating method, a dip coating method, and the like can be applied.
[0079] Drying process
[0080] After applying the coating solution, the coating is obtained by heating at any temperature to volatilize the solvent. The heating temperature is not particularly limited. In one example, it is preferably 60° C. or higher, and more preferably 80° C. or higher. The upper limit is appropriately selected according to the type of solvent. The heating can be performed multiple times at different temperatures. In addition, the drying process can be performed under any environment of atmospheric pressure, pressurized, or reduced pressure.
[0081] 2. Electrodes
[0082] The electrode of the present invention has the above-mentioned current collector and a composite material layer including an active material and a binder disposed on the current collector. The composite material layer is not particularly limited in type as long as it includes an active material and a binder, but preferably the binder includes a vinylidene fluoride homopolymer or a vinylidene fluoride polymer B, wherein the vinylidene fluoride polymer B includes a structural unit derived from vinylidene fluoride and a structural unit derived from hexafluoropropylene and / or a structural unit derived from a compound represented by the following general formula (2). The following describes each structure of the electrode.
[0083] Active substances
[0084] The active material contained in the composite material layer may be a positive electrode active material or a negative electrode active material, and is appropriately selected according to its application.
[0085] Examples of negative electrode active materials include: carbon materials such as artificial graphite, natural graphite, non-graphitizable carbon, easily graphitizable carbon, activated carbon, or materials obtained by calcining and carbonizing phenolic resin and asphalt; metal / alloy materials such as Cu, Li, Mg, B, Al, Ga, In, Si, Ge, Sn, Pb, Sb, Bi, Cd, Ag, Zn, Hf, Zr, and Y; and SiO, SiO 2 、GeO、GeO 2 、SnO、SnO 2 、PbO、PbO 2 , Li 4 Ti 5 O 12(LTO) and other metal oxides. In addition, the negative electrode active material may be a material on which a coating treatment is applied on the surface, and may contain one type alone or two or more types. It should be noted that the negative electrode active material may be a commercially available product.
[0086] On the other hand, examples of the positive electrode active material include lithium-based positive electrode active materials, such as lithium metal oxides represented by the following general formula (3), and materials having their surfaces subjected to coating treatment.
[0087] LiM x O 2 ……(3)
[0088] In the general formula (3), M represents at least one metal element including Ni, and as the metal element other than Ni, it is preferably selected from the group consisting of Co, Al, Fe, Mn, Cr and V. More preferably, in addition to Ni, it further contains one or more metals selected from the group consisting of Co, Mn and Al. In addition, in the lithium metal oxide represented by the above formula (3), when the total amount of the metal elements constituting M is 100 mol%, it is preferred to contain 55 mol% or more of Ni, and more preferably to contain 70% or more of Ni.
[0089] In the above general formula (3), 0.5≤x≤1.5, more preferably 0.7≤x≤1.3.
[0090] The composition examples of the lithium-based positive electrode active material represented by the general formula (3) and other lithium-based positive electrode active materials include: Li 1.0 Ni 0.8 Co 0.2 O 2 , Li 1.0 Ni 0.5 Mn 0.5 O 2 , Li 1.00 Ni 0.35 Co 0.34 Mn 0.34 O 2 (NCM111), Li 1.00 Ni 0.52 Co 0.20 Mn 0.30 O 2 (NCM523), Li 1.00 Ni 0.50 Co 0.30 Mn 0.20 O 2 (NCM532), Li 1.00 Ni 0.6 Co 0.2 Mn 0.2 O2 (NCM622), Li 1.00 Ni 0.83 Co 0.12 Mn 0.05 O 2 (NCM811), Li 1.00 Ni 0.85 Co 0.15 Al 0.05 O 2 (NCA811), LiCoO 2 (LCO), LiMn 2 O 4 (LMO), LiFePO 4 (LFP), LiMnPO 4 (LMP) and LiMn 1-x Fe x PO 4 (LFMP) etc. In addition, the positive electrode active material may be a material subjected to coating treatment on the surface thereof, and may contain one kind alone or two or more kinds. It should be noted that the positive electrode active material may be a commercially available product.
[0091] The amount of active material contained in the composite material layer is appropriately selected according to its type, electrode function, battery type, etc., without particular limitation, but in one example, it is preferably 50.0 mass % or more and 99.9 mass % or less relative to the total amount of the composite material layer. If the amount of active material is within this range, for example, sufficient charge and discharge capacity can be obtained, and battery performance tends to become good.
[0092] Adhesives
[0093] The binder contained in the composite material layer is not particularly limited as long as it can bond the above-mentioned active material, but as mentioned above, it preferably contains a vinylidene fluoride homopolymer or a vinylidene fluoride polymer B, wherein the vinylidene fluoride polymer B contains a structural unit derived from vinylidene fluoride and a structural unit derived from hexafluoropropylene and / or a structural unit derived from a compound represented by the following general formula (2). The binder may contain only a vinylidene fluoride homopolymer, or only a vinylidene fluoride polymer B, or both. Moreover, the vinylidene fluoride polymer B may contain only one or more than two.
[0094] The vinylidene fluoride homopolymer that can be used as an adhesive is the same as the known vinylidene fluoride homopolymer. The preparation method of the vinylidene fluoride homopolymer is not particularly limited, and vinylidene fluoride can be polymerized by a known method. Examples of polymerization methods include suspension polymerization, emulsion polymerization, solution polymerization, etc.
[0095] On the other hand, the vinylidene fluoride polymer B is a polymer comprising a structural unit derived from vinylidene fluoride and a structural unit derived from hexafluoropropylene and / or a structural unit derived from a compound shown in the general formula (2). The vinylidene fluoride polymer B can be, for example, a copolymer of vinylidene fluoride and hexafluoropropylene, a copolymer of vinylidene fluoride and a compound shown in the general formula (2), or a copolymer of vinylidene fluoride, hexafluoropropylene and a compound shown in the general formula (2). In addition, the vinylidene fluoride polymer B may contain other copolymer components within the scope of not damaging the purpose and effect of the present invention.
[0096] The amount of structural units derived from vinylidene fluoride in the vinylidene fluoride polymer B is preferably 50 mol% or more, more preferably 60 mol% or more, and particularly preferably 80 mol% or more relative to the amount (molar) of all structural units constituting the vinylidene fluoride polymer B. When the amount of structural units derived from vinylidene fluoride is 50 mol% or more, it is easy to obtain properties derived from vinylidene fluoride, such as electrochemical stability. The amount of structural units derived from vinylidene fluoride in the vinylidene fluoride polymer B can be determined by 19 Determined by F-NMR.
[0097] On the other hand, the amount of the structural unit derived from hexafluoropropylene in the vinylidene fluoride polymer B is more preferably 10 mol% or less relative to the amount (moles) of all structural units constituting the vinylidene fluoride polymer B. When the amount of the structural unit derived from hexafluoropropylene is within the above range, the melting point of the vinylidene fluoride polymer B is likely to fall within the desired range, and the bonding strength between the vinylidene fluoride polymer B and the above-mentioned active material etc. is improved. The amount of the structural unit derived from hexafluoropropylene in the vinylidene fluoride polymer B can be adjusted by 19 Determined by F-NMR.
[0098] Next, the general formula (1) is shown below: The vinylidene fluoride polymer B may contain only one type of structural unit derived from the compound represented by the general formula (2) above, or may contain two or more types.
[0099] [Chemical formula 6]
[0100]
[0101] In the above general formula (2), R 4 represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or a carboxyl group substituted with an alkyl group having 1 to 5 carbon atoms. The carboxyl group substituted with an alkyl group having 1 to 5 carbon atoms refers to a carboxyl group represented by -C(=O)-OC n H 2n+1 A group represented by (wherein n is 1 or more and 5 or less). From the viewpoint of polymerization reactivity, R 4 Preferably, it is a hydrogen atom, a methyl group or -C(=O)-OCH 3.
[0102] In addition, R 5 and R 6 Each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and from the viewpoint of polymerization reactivity, a substituent having less steric hindrance is preferred, preferably hydrogen or an alkyl group having 1 to 3 carbon atoms, and more preferably hydrogen or a methyl group.
[0103] Furthermore, X in the above general formula (2) 2 It represents a single bond or a divalent atomic group having 1 to 20 atoms in the main chain and a molecular weight of 500 or less. 2 The number of atoms in the main chain refers to the number of atoms in the shortest chain connecting the terminal carboxyl group and the carbon-carbon double bond in the general formula (2). The number of atoms in the main chain is more preferably 15 or less.
[0104] By the above X 2 The structure of the atomic group represented is not particularly limited as long as its molecular weight is less than 500 and satisfies the number of atoms in the above main chain, and it can be straight chain, branched chain, or include a ring structure. Examples of the structure constituting the above atomic group include alkylene, carbonyl (-C(=O)-, ether bond (-O-), aromatic ring, and alicyclic structure.
[0105] Specific examples of the compound represented by the general formula (2) include the compound represented by the general formula (1) above, and also include monomethyl maleate (MMM), acrylic acid (AA), methacrylic acid, and the like.
[0106] The amount of the structural units derived from the compound represented by the general formula (2) is preferably 0.01 mol% or more and 10 mol% or less, more preferably 0.02 mol% or more and 7 mol% or less, and particularly preferably 0.03 mol% or more and 4 mol% or less, relative to the amount (mol) of all structural units constituting the vinylidene fluoride polymer B. When the amount of the structural units derived from the compound represented by the general formula (2) is 0.01 mol% or more, the bonding strength between the binder and the active material and the bonding strength between the composite material layer and the coating are improved. On the other hand, when the amount of the structural units derived from the compound represented by the general formula (2) is 10 mol% or less, the amount of the structural units derived from vinylidene fluoride is relatively increased, and the electrochemical stability of the composite material layer is likely to be good. The amount of the structural units derived from the compound represented by the general formula (2) in the vinylidene fluoride polymer B can be adjusted by 19 F-NMR, 1 Analyze by H-NMR etc.
[0107] In addition, as described above, the vinylidene fluoride polymer B may partially contain structural units of compounds other than vinylidene fluoride, hexafluoropropylene and the compound represented by the general formula (2) (hereinafter also referred to as "other compounds") within the scope that does not impair the purpose and effect of the present invention. Specific examples of other compounds include other compounds listed in the description of the above-mentioned vinylidene fluoride polymer A. The amount of structural units derived from other compounds is preferably 10 mol% or less relative to the amount (moles) of all structural units constituting the vinylidene fluoride polymer B. When the amount of structural units derived from other compounds in the vinylidene fluoride polymer B is 10 mol% or less, the electrochemical stability of the composite material layer is easily improved, and the bonding strength between the composite material layer and the coating layer is easily improved. The amount of structural units derived from other compounds can be adjusted by 19 F-NMR, 1 Analyze by H-NMR etc.
[0108] The preparation method of the vinylidene fluoride polymer B is not particularly limited, and vinylidene fluoride and hexafluoropropylene and / or the compound represented by the general formula (2) may be polymerized by a known method. Examples of the polymerization method include suspension polymerization, emulsion polymerization, solution polymerization, and the like.
[0109] In addition, the amount of the adhesive in the composite layer is appropriately selected according to the composition of the adhesive, the function of the electrode, the type of the battery, etc., without particular limitation, but in one example, relative to the total amount of the composite layer, preferably 0.1% by mass or more and 50% by mass or less. When the amount of the adhesive is within this range, the bonding strength between the composite layer and the coating is good. In addition, since the amount of the active material becomes relatively sufficient, sufficient charge and discharge capacity can be obtained, and the battery performance is easy to be good.
[0110] Other ingredients
[0111] The composite material layer may further include known dispersants, adhesive aids, tackifiers, etc. within the scope that does not impair the purpose and effect of the present invention. Furthermore, it may further include: nitrogen compounds such as phosphorus compounds, sulfur compounds, organic acids, amine compounds, and ammonium compounds; organic esters, various silane-based, titanium-based, and aluminum-based coupling agents; polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), and polyacrylonitrile (PAN) and other resins. Among them, their total amount is preferably 15% by mass or less relative to the total amount of the composite material layer.
[0112] ·Method for forming composite material layer
[0113] The composite material layer can be formed by applying a composite material slurry containing the above-mentioned active material, a binder or other components as required, and a solvent on the above-mentioned coating layer of the current collector by a known method, and drying it by a known method.
[0114] 3. Battery
[0115] The above-mentioned current collector and electrode can be used in various lithium-ion secondary batteries and the like, but can also be used in other applications.
[0116] Example
[0117] Hereinafter, specific examples of the present invention will be described together with comparative examples, but the present invention is not limited thereto.
[0118] 1. Preparation of Materials
[0119] The following materials were prepared.
[0120] (vinylidene fluoride polymer)
[0121] [Preparation Example 1]
[0122] In an autoclave with a content of 2 liters, 1096 g of ion exchange water, 0.2 g of Metolose 90SH-100 (manufactured by Shin-Etsu Chemical Co., Ltd.), 2.2 g of a 50% by mass diisopropyl peroxydicarbonate-HFE-347pc-f solution, 1.3 g of ethyl acetate, 426 g of vinylidene fluoride, and 0.2 g of the initial addition amount of succinic acid acryloyloxyethyl ester (AES) were added, and the temperature was raised to 26°C in 1 hour. Then, while maintaining 26°C, a 6% by mass aqueous solution of succinic acid acryloyloxyethyl ester was slowly added at a rate of 0.5 g / min. The obtained polymer slurry was dehydrated and dried to obtain a vinylidene fluoride copolymer (VDF / AES) containing polar groups. Acryloyloxyethyl succinate, including the amount initially added, was added in a total amount of 4.3 g.
[0123] [Preparation Example 2]
[0124] In an autoclave with a content of 2 liters, 1085 g of ion exchange water, 0.2 g of Metolose SM-100 (manufactured by Shin-Etsu Chemical Co., Ltd.), 1.3 g of a 50% by mass diisopropyl peroxydicarbonate-HFE-347pc-f solution, 2.1 g of ethyl acetate, and 424 g of vinylidene fluoride (VDF) were placed, and the temperature was raised to 26° C. over 1 hour. Then, polymerization was performed while maintaining 26° C. The obtained polymer slurry was dehydrated and dried to obtain a vinylidene fluoride polymer (PVDF).
[0125] [Preparation Example 3]
[0126] In an autoclave with a content of 2 liters, 1092 g of ion exchange water, 0.2 g of Metolose 90SH-100 (manufactured by Shin-Etsu Chemical Co., Ltd.), 3.6 g of a 50% by mass diisopropyl peroxydicarbonate-HFE-347pc-f solution, 5.3 g of ethyl acetate, 423 g of vinylidene fluoride, and 0.2 g of the initial addition amount of succinic acid acryloyloxyethyl ester (AES) were loaded, and the temperature was raised to 26°C in 1 hour. Then, while maintaining 26°C, a 5% by mass aqueous solution of succinic acid acryloyloxyethyl ester was slowly added at a rate of 0.6 g / min. The obtained polymer slurry was dehydrated and dried to obtain a vinylidene fluoride copolymer (VDF / AES) containing polar groups. Acryloyloxyethyl succinate, including the amount initially added, was added in a total amount of 4.2 g.
[0127] [Preparation Example 4]
[0128] In an autoclave with a content of 2 liters, 1081 g of ion exchange water, 0.8 g of Metolose SM-100 (manufactured by Shin-Etsu Chemical Co., Ltd.), 2.0 g of a 50% by mass diisopropyl peroxydicarbonate-HFE-347pc-f solution, 12.9 g of hexafluoropropylene (HFP), 415 g of vinylidene fluoride (VDF), and 1.3 g of monomethyl maleate (MMM) were placed, and the temperature was raised to 29° C. in 1 hour. Then, polymerization was carried out while maintaining 29° C. The obtained polymer slurry was dehydrated and dried to obtain a vinylidene fluoride copolymer (VDF / HFP / MMM).
[0129] [Preparation Example 5]
[0130] In an autoclave with a content of 2 liters, 1091 g of ion exchange water, 0.2 g of Metolose SM-100 (manufactured by Shin-Etsu Chemical Co., Ltd.), 5.1 g of a 50% by mass diisopropyl peroxydicarbonate-HFE-347pc-f solution, 7.7 g of ethyl acetate, and 426 g of vinylidene fluoride (VDF) were placed, and the temperature was raised to 26° C. over 1 hour. Then, polymerization was performed while maintaining 26° C. The obtained polymer slurry was dehydrated and dried to obtain a vinylidene fluoride polymer (PVDF).
[0131] [Preparation Example 6]
[0132] In an autoclave with a content of 2 liters, 1009 g of ion exchange water, 0.2 g of Metolose SM-100 (manufactured by Shin-Etsu Chemical Co., Ltd.), 5.1 g of a 50% by mass diisopropyl peroxydicarbonate-HFE-347pc-f solution, 9.3 g of ethyl acetate, 420 g of vinylidene fluoride (VDF), and 0.2 g of an initial addition amount of succinic acid acryloyloxyethyl ester (AES) were added, and the temperature was raised to 26°C in 1 hour. Then, while maintaining 26°C, a 5% by mass aqueous solution of succinic acid acryloyloxyethyl ester was slowly added at a rate of 0.7 g / min. The obtained polymer slurry was dehydrated and dried to obtain a vinylidene fluoride copolymer (VDF / AES) containing polar groups. Acryloyloxyethyl succinate, including the amount initially added, was added in a total amount of 4.2 g.
[0133] [Preparation Example 7]
[0134] In an autoclave with a content of 2 liters, 987 g of ion exchange water, 0.2 g of Metolose SM-100 (manufactured by Shin-Etsu Chemical Co., Ltd.), 8.8 g of a 50% by mass diisopropyl peroxydicarbonate-HFE-347pc-f solution, 0.8 g of ethyl acetate, 405 g of vinylidene fluoride (VDF), and 4.1 g of monomethyl maleate (MMM) were added, and the temperature was raised to 29° C. in 1 hour. Then, polymerization was carried out while maintaining 29° C. The obtained polymer slurry was dehydrated and dried to obtain a vinylidene fluoride copolymer (VDF / MMM) containing a polar group.
[0135] [Preparation Example 8]
[0136] In an autoclave with a content of 2 liters, 900 g of ion exchange water, 0.4 g of hydroxypropyl methylcellulose, 2 g of butyl peroxy pivalate, 396 g of vinylidene fluoride, and 0.2 g of the initial addition amount of acrylic acid were loaded and heated to 50 ° C. Under the condition of keeping the pressure constant during the polymerization, a 1 wt % acrylic acid aqueous solution containing acrylic acid was continuously supplied to the reaction vessel. The obtained polymer slurry was dehydrated and dried to obtain a vinylidene fluoride copolymer (VDF / AA) containing a polar group. Acrylic acid, including the amount initially added, was added in a total amount of 4 g.
[0137] 2. Preparation of electrodes (Example 1)
[0138] ·Coating production
[0139] The coating vinylidene fluoride polymer shown in Table 1 was dissolved in N-methyl-2-pyrrolidone (hereinafter referred to as NMP) to prepare a vinylidene fluoride polymer solution containing 6% by mass of the vinylidene fluoride polymer. Then, Super-P and NMP manufactured by Timcal Japan (Co., Ltd.) were added to the polymer solution as conductive aids to adjust the solid content concentration to 4% by mass of the coating solution. The mass ratio of Super-P to the vinylidene fluoride polymer in the coating solution was 50:50. The obtained coating solution was applied to an aluminum foil (substrate) with a thickness of 15 μm as a collector using a TH-C type coating machine manufactured by THANK METAL (Co., Ltd.), and after drying, a unit area weight of 1.4 g / m 2 coating.
[0140] ·Production of composite material layers
[0141] The composite material layer vinylidene fluoride polymer shown in Table 1 was dissolved in NMP to prepare a vinylidene fluoride polymer solution containing 6% by mass of the vinylidene fluoride polymer. Then, a CNT (carbon nanotube) dispersion (containing a tube diameter of 7 nm and a specific surface area of 300 m2) as a conductive additive was added to the polymer solution. 2 / g MWCNT (multi-walled carbon nanotube) 4.3 mass % NMP mixed solution) and NMP were kneaded. Then, LFP (lithium iron phosphate: primary particle size: D50: 2 μm, specific surface area: 19.9 m 2 / g), the solid content concentration is 55% by mass, and the composite material slurry is adjusted by kneading. The mass ratio of the positive electrode active material, CNT and vinylidene fluoride polymer in the composite material slurry is 100:2:2. The obtained composite material slurry is applied on the above-mentioned coating layer using a TH-C type coating machine manufactured by THANK METAL Co., Ltd., and after drying, the unit area weight is about 150g / m 2 of composite material layers.
[0142] (Examples 2 to 10 and Comparative Examples 1 to 2)
[0143] An electrode was prepared in the same manner as in Example 1 except that the type and amount of the vinylidene fluoride polymer in the coating solution for forming the coating layer and the type and amount of the vinylidene fluoride polymer in the composite material slurry for forming the composite material layer were changed as shown in Table 1.
[0144] (Reference example)
[0145] An electrode was produced in the same manner as in Example 1 except that the composite material layer was directly formed on the substrate without forming a coating layer.
[0146] 3. Evaluation
[0147] The measurement and evaluation of various physical properties were performed as follows.
[0148] ·Measurement of reduced logarithmic viscosity
[0149] The reduced logarithmic viscosity of the vinylidene fluoride polymer used in the above examples and comparative examples was measured as follows. First, 80 mg of the vinylidene fluoride polymer was dissolved in 20 mL of N,N-dimethylformamide, and the viscosity was measured using an Ubbelohde viscometer in a constant temperature bath at 30 °C. Then, based on the obtained value, the reduced logarithmic viscosity (η i ) of the vinylidene fluoride polymer was calculated according to the following formula.
[0150] η i =(1 / C)·ln(η / η 0 )
[0151] It should be noted that in the above formula, η is the viscosity of the solution, η 0 is the viscosity of the solvent N,N-dimethylformamide alone, and C is the concentration of the vinylidene fluoride polymer, which is 0.4 g / dL.
[0152] ·Electrode state
[0153] After the composite material layer was formed, the composite material layer was visually observed. Those with cracks were marked as ×, those with slight cracks were marked as Δ, and those without cracks were marked as 〇. The electrode was pressed using a roller press to adjust the electrode density to 2.3 g / cm 3 . At this time, the cracks in the composite material layer with an electrode state of Δ were repaired, and no cracks were observed anymore. On the other hand, even if the same roller pressing was performed on the composite material layer with an electrode state of ×, the cracks were not repaired.
[0154] ·Measurement of peel strength
[0155] After roller pressing, the peel strength was measured for the electrodes without observed cracks (electrodes with electrode states of 〇 and Δ). They were cut into a length of 50 mm and a width of 20 mm, and according to JIS K6854-1, a 90-degree peel test was performed using a tensile testing machine (“STB-1225S” manufactured by A&D Co., Ltd.) at a chuck speed of 10 mm / min to measure the peel strength (gf / mm). It should be noted that for specimens with low peel strength that were peeled from the substrate before measurement, it was marked as “unmeasurable”.
[0156] [Table 1]
[0157]
[0158]
[0159] As shown in Table 1 above, in Examples 1 to 10 having a coating on a substrate, the coating comprises: a vinylidene fluoride polymer A comprising structural units derived from vinylidene fluoride and structural units derived from a compound represented by the above general formula (1), and a conductive aid, and the peel strength is improved compared to the case where the substrate does not include a coating.
[0160] In addition, when the vinylidene fluoride polymer in the coating layer does not include a structural unit derived from the compound represented by the general formula (1), cracks appear on the surface of the composite material layer (Comparative Examples 1 and 2). In contrast, when the vinylidene fluoride polymer includes a structural unit derived from the compound represented by the general formula (1), no cracks appear (Examples 1 to 4, Examples 6 to 10), or although slight cracks are observed, the cracks are no longer visible by rolling (Example 5).
[0161] This application claims the priority of Japanese Patent Application No. 2022-156630 filed on September 29, 2022. The contents described in that application specification are incorporated herein by reference in their entirety.
[0162] Industrial Applicability
[0163] When the collector of the present invention is formed with a composite material layer on the collector to form an electrode, cracks are less likely to occur on the electrode surface, and high-quality electrodes and batteries can be manufactured. Therefore, it is very useful in the manufacture of lithium-ion secondary batteries and the like.
Claims
1. A current collector, wherein: The current collector has: a substrate comprising a metal; and a coating disposed on at least one surface of the substrate, The coating layer comprises: a vinylidene fluoride polymer A comprising a structural unit derived from vinylidene fluoride and a structural unit derived from a compound represented by the following general formula (1), and a conductive auxiliary agent. [Chemical formula 1] In the general formula (1), R 1 , R 2 and R 3 each independently represents a hydrogen atom, a chlorine atom, a fluorine atom or an alkyl group having 1 to 5 carbon atoms, X 1 It represents a divalent atomic group having 1 to 6 atoms in the main chain and a molecular weight of 156 or less.
2. The current collector according to claim 1, wherein When the total amount of the vinylidene fluoride polymer A and the conductive aid in the coating layer is 100 parts by mass, the amount of the vinylidene fluoride polymer A is 65 parts by mass or less.
3. An electrode comprising: The current collector according to claim 1 or 2; and A composite material layer including an active material and a binder is disposed on the coating layer of the current collector.
4. The electrode according to claim 3, wherein The adhesive comprises a vinylidene fluoride homopolymer and / or a vinylidene fluoride polymer B, The vinylidene fluoride polymer B comprises a structural unit derived from vinylidene fluoride and a structural unit derived from hexafluoropropylene and / or a structural unit derived from a compound represented by the following general formula (2): [Chemical formula 2] In the general formula (2), R 4 represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or a carboxyl group substituted by an alkyl group having 1 to 5 carbon atoms, R 5 and R 6 each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, X 2 It represents a single bond or a divalent atomic group having 1 to 20 atoms in the main chain and a molecular weight of 500 or less.
5. A battery comprising the electrode according to claim 3.
6. A method for producing a current collector, comprising the step of coating at least one surface of a substrate comprising a metal with a coating solution comprising a vinylidene fluoride polymer a and a solvent, The vinylidene fluoride polymer a comprises a structural unit derived from vinylidene fluoride and a structural unit derived from a compound represented by the following general formula (1a), [Chemical formula 3] In the general formula (1a), R 1a , R 2a and R 3a each independently represents a hydrogen atom, a chlorine atom, a fluorine atom or an alkyl group having 1 to 5 carbon atoms, X 1a It represents a divalent atomic group having 1 to 6 atoms in the main chain and a molecular weight of 156 or less.
Citation Information
Patent Citations
Grease composition for control cable and control cable
JP2022156630A
Collector, electrode structure, nonaqueous electrolyte battery, and electricity storage component
WO2013151046A1